Clinical trial parameters that influence outcomes in lupus trials that use the systemic lupus erythematosus responder index. (17th October 2017) - Kalunian, Kenneth C; Urowitz, Murray B; Isenberg, David; Merrill, Joan T; Petri, Michelle; Furie, Richard A; Morgan-Cox, Mary-Ann; Taha, Rebecca; Watts, Steven; Silk, Maria; Linnik, Matthew D
Abstract: Objective: The SLE Responder Index (SRI) is a composite endpoint used in SLE trials. This investigation examined the clinical trial elements that drive response measured by the SRI. Methods: Analyses are based on data from two phase 3 trials ( n = 2262) that evaluated the impact of an anti-B-cell activating factor antibody on disease activity using SRI-5 as the primary endpoint (ClinicalTrials.gov NCT01196091 and NCT01205438). Results: The SRI-5 response rate at week 52 for all patients was 32.8%. Non-response due to a lack of SLEDAI improvement, concomitant medication non-compliance or dropout was 31, 16.5 and 19.1%, respectively. Non-response due to deterioration in BILAG or Physician's Global Assessment after SLEDAI improvement, concomitant medication compliance and trial completion was 0.5%. Disease activity in three SLEDAI organ systems was highly prevalent at baseline: mucocutaneous, 90.6%; musculoskeletal, 82.9%; and immunologic, 71.6%. Disease activity in each of the other organ systems was <11% of patients. Four clinical manifestations were highly prevalent at baseline: arthritis, 82.6%; rash, 69.2%; alopecia, 58.2%; and mucosal ulcer, 32.5%. The combined prevalence of renal, vascular and CNS disease at baseline was 17.6%; these patients had high SRI-5 response rates. Adjustments to corticosteroids were allowed during the first 24 weeks. Increases in corticosteroids above 2.5 mg/day were observed in 16.2% of placebo patients over the first 24 weeks after randomization. Conclusion: The primary drivers of SRI-5 response were SLEDAI improvement, concomitant medication adherence and trial completion. Arthritis, rash, alopecia and mucosal ulcer were the most prevalent clinical manifestations at baseline. Corticosteroid increases and rare, highly weighted disease manifestations in SLEDAI can confound the SRI signal.